M16 the history of Secret Intelligence Service, 1909-1949 - Jeffret, Keith (Bloomsbury, 2010)
Part One: Early Days -- 1. The beginnings of the service -- Part Two: The First World War -- 2. Status, organisation and expertise -- 3. Operations in the West -- 4. Working further afield -- Part Three: The Interwar Years -- 5. The emergence of SIS -- 6. From Boche to Bolsheviks -- 7. Domestic matters -- 8. Existing on a shoestring -- 9. Approaching war -- Part Four: The Impact of War -- 10. Keeping afloat -- 11. The European theatre -- 12. From Budapest to Baghdad -- 13. West and East -- Part Five: Winning the War: 14. The tide turns -- 15. From Switzerland to Normandy -- 16. Victory in Europe -- 17. Asia and the end of the war -- 18. Postwar planning -- Part Six: From Hot War to Cold War: -- 19. Adjusting to peace -- 20. Deployment and operations in Europe -- 21. A worldwide Service -- Part Seven: Conclusion. -- 22. SIS: Leadership and performance over the first forty years.